Prospective vocational teachers in 21st century learning: challenges and opportunities - Nuur Wachid Abdul Majid (Universitas Pendidikan Indonesia (UPI), 2019)
Vocational graduates are expected to be the biggest contributors to skilled workforce and can compete with others. However, there are several factors in the high unemployment rate among SMKs, it is necessary to examine the reasons why there are still many SMK graduates unemployed. The government and stakeholders must strive to increase employment opportunities to accommodate graduates. This is very reasonable because the absorption of graduates is very low, considering the number of industries that accommodate vocational graduates is still little or not in accordance with the interests and talents of graduates. The problem of vocational teachers who do not master the teaching field is an important factor, because the teacher is the spearhead in delivering material in accordance with the curriculum prepared by the government. The problem will be complicated if the teacher factor is not handled properly. Opportunities for prospective vocational teachers are very high, because the Ministry of Education and Culture prioritizes the opening of vocational schools. However, this opportunity must be balanced with quality competencies according to school needs. This is a part of the challenge of the LPTK students, because the Ministry of Education and Culture has planned to take productive teachers from more experienced industries. So the opportunities for vocational teacher candidates face obstacles.